PEMAHAMAN HADITS MENURUT MUHAMMAD AL-GHAZALI - Sugihardi Sugihardi (Adisam Publisher, 2025)
Hadith is the main source of Islamic teachings after the Qur'an. To understand hadith deeply, a comprehensive study is needed with the right methods and approaches so that the intent and substance in each hadith can be revealed properly. Along with the times, contemporary scholars continue to try to formulate an understanding of hadith with various methods. One of them is Muhammad Al- Ghazali, who proposed a number of methods of understanding the hadith of the Prophet Muhammad. The method of understanding hadith proposed by Muhammad al-Ghazali, as outlined in his book ‘as-Sunnah an-Nabawiyah’, provides a significant contribution in solving various problems faced by Muslims today. Al-Ghazali emphasised that the understanding of hadith must fulfil four criteria for the validity of the hadith matan, first: The hadith matan must be in accordance with the Qur'an, second: the hadith matan must be in accordance with other sahih hadith, third: the hadith matan must be in harmony with historical facts, fourth: the hadith matan must be in accordance with scientific truth. Thus, hadiths that contradict the principles of the teachings of the Qur'an, historical facts, and scientific truth according to him must be rejected.